Defect Passivation via a Graded Fullerene Heterojunction in Low-Bandgap Pb–Sn Binary Perovskite Photovoltaics - Rajagopal, Adharsh; Liang, Po-Wei; Chueh, Chu-Chen; Yang, Zhibin; Jen, Alex K.-Y (ACS energy letters, 2017)
Development of low-bandgap (∼1.2 eV) Pb–Sn binary perovskites is exciting and has recently gained immense attention because of their high photovoltages, lowered Pb toxicity, and pivotal role in realizing perovskite tandem solar cells. Defect passivation in this class of perovskite alloys has immense potential to further reduce the photovoltage deficit but is relatively unexplored. Here, we investigate and report the passivation of defect sites in low-bandgap CH3NH3Pb0.5Sn0.5I3 perovskite through the incorporation of fluoroalkyl-substituted fullerene (DF-C60) via a graded heterojunction (GHJ) structure. Graded distribution of DF-C60 successfully reduced the number of trap sites, and the resultant films had characteristically lower Urbach energy, dominant bimolecular recombination, and higher surface/bulk recombination resistance. The improved optoelectronic quality of films with GHJ structure was reflected in improved performance for corresponding photovoltaic devices, with the best PCE up to 15.61% and a remarkably high V oc of 0.89 V. A V oc of ∼92% of the Shockley–Queisser (SQ) limit achieved here is comparable to that of state-of-the-art inorganic technologies and is the best among perovskite solar cells (PVSCs) to date. Additionally, through stability studies, we find that though GHJ with DF-C60 can slow down degradation due to moisture penetration, the oxidative susceptibility of Sn in binary perovskites sharply constraints overall stability.